HUBUNGAN ANTARA SELF-CONCEPT TERHADAP MATEMATIKA DENGAN KEMAMPUAN BERPIKIR KREATIF MATEMATIK SISWA - Risqy Rahman (IKIP Siliwangi and I-MES, 2012)
This study aimed to examine and describe the creative thinking relationship with the self-concept is a survey research design. To get the research data used instrument in the form of creative thinking ability tests and students' self-concept scale. The study population was all students of SMP Negeri 13 Jakarta with seventh grade students study sample as many as two classes were selected by cluster random sampling. The data were analyzed quantitatively. Quantitative analysis was conducted on the ability to think creatively and data self-concept. The instruments used were 12 creative thinking ability test questions and 31 statements about the self-concept. In a trial calculation using the program Anates instruments and statistical calculations using SPSS 18. Results showed that self-concept affects students' ability to think creatively.